A study on future roles of insurance brokers from customer-oriented perspective / Nor Jamila Hamdan - Hamdan, Nor Jamila (Faculty of Business and Management, 2010)
Fundamental changes in the market environment force insurance intermediaries to redefine their roles. This study focuses on the future functions of brokers, which are analyzed from a functional as well as a customer-oriented perspective. To cope with the limitation of current intermediation research, the customer-value approach is applied as an alternative framework. This approach suggests that brokers must create benefit and customer value to be successful in the future. After a review with literature concerning insurance intermediation, this study presents the result of survey conducted to 50 respondents of clients of insurance broker specified in Kuala Lumpur area, representing important current and potential customers of insurance brokers. The findings highlight three main functions insurance brokers are expected to fulfil for their customers: service, price and relationship. This study concludes with suggestions for further essential requirements for brokers that will enable them to meet the future needs of their clients in the most optimal manner.